Analysis on the Impact of Water Intake and Consumption on the Runoff of Mainstream of the Yellow River - QI Yonghui; Chelimuge; YU Huanghao; QIAN Yu; LI Binquan (Renmin Zhujiang)
Water intake and water consumption have an important impact on the runoff of the Yellow River Basin.Based on the measured runoff data from the main control stations of the mainstream of the Yellow River and its water resources bulletin data,this paper preliminarily analyzes the runoff changes of the main sections of the upper and lower reaches of the mainstream and the impact of water intake and consumption on the mainstream runoff.The results show that:①The annual runoff measured at all three stations,namely Lanzhou (1919—2018),Huayuankou (1919—2018),and Lijin (1950—2018),shows a decreasing trend,with non-significant decrease in Lanzhou station in the upper reaches,but significant decrease in the two stations in the middle and lower reaches.②During the period of 1998—2019,the annual runoff of the 11 main hydrological stations on the mainstream of the Yellow River shows a consistent increasing trend,which may results from the increase in average precipitation in the basin.③The changes in water intake and total water consumption in the basin from 1998 to 2019 show an increasing trend,indicating that the water intake along the Yellow River increases steadily.The influence of water intake and consumption on the runoff changes in the section above Lanzhou is small,with the contribution less than 20%.In the middle and lower reaches,the impact of water intake and consumption on the reservoir storage is big,especially in the Longmen-Sanmenxia subarea,where the proportion of restored surface runoff to the natural river runoff reaches 55.4%.